2020
DOI: 10.17159/2411-9717/1196/2020
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analysis of the Brumadinho tailings disaster using advanced geospatial analytics

Abstract: On 25 January 2019, one of the most significant and deadliest tailings dam failures in history occurred at Brumadinho Córrego do Feijão iron ore mine in Brazil. Twelve million cubic metres of tailings travelling at 120 km/h destroyed a total of 109 buildings, 36 belonging to Vale and 73 local residences. More than 259 people died. Some farmlands were wiped out and left under a sea of mud and tailings up to 8 m deep. Seven sections of local roads, one main road, and one railway bridge were severely damaged. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Robertson et al [7] provide only a little information about the affected infrastructure but mention 100 m of destroyed railway in addition to the railway bridge. Atif et al [27] reported 109 affected buildings in their analysis of the disaster, showing only minor discrepancies with the calculated number based on OSM. The benefit of OSM data lies in its free data availability and its large user community.…”
Section: Results Of the Risk Assessmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Robertson et al [7] provide only a little information about the affected infrastructure but mention 100 m of destroyed railway in addition to the railway bridge. Atif et al [27] reported 109 affected buildings in their analysis of the disaster, showing only minor discrepancies with the calculated number based on OSM. The benefit of OSM data lies in its free data availability and its large user community.…”
Section: Results Of the Risk Assessmentmentioning
confidence: 90%
“…As mentioned before, other tailings breach models have already been applied for the incident in Brumadinho, but none of them provides numerical information about its accuracy, making it difficult to benchmark the Tailings Flow Model [12,14,27]. The power of this empirical model lies in its simplicity and highly aggregated information content coming from the build-in risk assessment.…”
Section: Discussion Of the Spatial Modellingmentioning
confidence: 99%